Pattern of Food Cravings in Pregnant Women Receiving Antenatal Care in a Community Setting (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Food cravings are a sudden desire to eat certain types of foods during pregnancy. Worldwide, it is a common phenomenon.Objectives: To find out the pattern of craving foods and examine to what extent the craving desires were fulfilled.Methods: This cross-sectional study was conducted among 150 pregnant women in a community setting. Data were collected during January to March 2020 by face-to-face interview with a semi-structured questionnaire. Sample women were selected purposively.Results: Mean age of the sample women was 23.59 (±4.36) years. 78% (117) of the respondents had cravings for one or more foods. Of them, 29.9% women had craved for sour fruits and 32.5% women had craved for milk-based sweets. Besides, 15.4%, 17.1% and 20.5% women had craved yogurt with misti, rice-milk-banana mixed and pickles respectively. Another 1.7% women had craved for non-food substance burnt clay. 23.9% craving desires was due to inhibiting nausea and 57.3% had no explanation. 70.9% craving desires was fulfilled. The proportion of fulfillment of craving desires was 100% in higher income families (p